Design of Acoustic Transmission Loss Measurements in the Form of Power Amplifier Based on Impedance Tube Method - Wahyu Setyawan; Solly Aryza; Adi Sastra P. Tarigan (CERED Indonesia Institute, 2022)
The conventional amplifier involves a power supply (ground) line connected to the audio path. This In the processing of the audio signal will appear IHM (Interval Hum Modulation) noise. Therefore, to be able to suppress the occurrence of noise to a minimum, then made an amplifier that does not refer to a ground power supply. The amplifier must really balance from input to output. To realize the balance amplifier is specified class AB push-pull specification with arms power of 120 Watt and bandwidth width between 50 to 10kHz. In the power amplifier used complementary pairs circuit system as a current amplifier. Based on the test results turned out output power to the speaker only 100 Watt with 20 volt supply voltage and has a bandwidth width between 30 Hz to 15 Hz with a gain of 163 times.